Study of the Associations between Color Doppler Ultrasound Grading of Hyperthyroidism and Biochemical Data on Thyroid Function - Lingyun Zhang; Jie Li; Suzhen Zhang; Chen Su; Zengcun Su; Yuezhong Zhang; Yonghao Gai; Shanshan Shao; Jianzhi Li; Guoquan Zhang (International Journal of Endocrinology)
Objective. The main study objective was to investigate the correlation between the color Doppler ultrasound grading of hyperthyroidism and the biochemical data of thyroid function. Methods. Seventy-six patients were diagnosed with hyperthyroidism based on clinical and laboratory data at our hospital. The patients were examined using color Doppler ultrasound and laboratory investigations before starting 131I treatment. First, patients were divided into two groups based on the blood flow distribution determined by ultrasound. If the blood flow signal in the parenchyma was scattered and thinned, with dispersive points and discontinuous streaky distribution, the blood flow distribution area in the sample frame was less than or equal to 1/2 of the sample frame area and was judged to be level 1. If the parenchyma was filled with diffuse blood flow signals or if most areas had depicted rich blood flow distribution when the area of blood flow distribution in the sampling frame was greater than 1/2 of the sampling frame area, it was judged to be level 2. Then, the correlations between color Doppler ultrasound grading and biochemical data of thyroid function were analyzed. The indices included FT3, FT4, TSH, anti-TG, anti-TPO, and TRAb. Parameters of thyroid homeostasis, including thyroid’s secretory capacity (SPINA-GT), the total deiodinase activity (SPINA-GD), Jostel’s TSH index, and the thyrotroph thyroid hormone sensitivity index (TTSI), were calculated and compared. Results. Correlations were noted between color Doppler ultrasound grading and FT3, FT4, TRAb, SPINA-GT, TSHI, and TTSI. Moreover, FT3, FT4, TRAb, SPINA-GT, TSHI, and TTSI were higher in level 2 patients compared with level 1 patients. Conclusion. Correlations were noted between color Doppler ultrasound grading and biochemical data of thyroid function.